Experimental study on the aluminum alloy 7075 during turning under dry and minimal quantity lubrication conditions - Abdul Rahman Abdul Ghani (Kulliyyah of Engineering, International Islamic University Malaysia, |, 2021)
Aluminum alloys Al7075-T651 is non-ferrous metal with great properties of light in weight and high strength which offers wide opportunity to wide range of applications. Currently, Al7075-T651 is used to manufacture components, gear and shaft in various industries such as automotive, aerospace and military. The rise of cutting temperature during machining in the manufacturing of the components contribute to the deterioration in the surface integrity of aluminum alloys. Ductility is one of the characteristics of the material that contributes to built-up-edge (BUE) and built-up-layer (BUL) on the cutting tool. The continuous formation of BUE in cutting operation alters the geometry of the cutting tool and consequently accelerates the tool wear progression. Chips produced during machining are simultaneously affecting the machining performance. Intensity of the BUE in dry machining not only contributed to different types of wear on the cutting tool but also lead to poor surface finish of the machined components. Minimum quantity lubrication (MQL) machining of aluminum alloys is predicted to be able to suppress the poor machining output effect during machining aluminum alloys. This study investigates the performance of uncoated carbide cutting tool in dry and MQL machining of Al7075-T651. The study aims to analyze the effect of tool performance on surface roughness and chip morphology in dry and MQL machining of Al7075-T651. 18 experimental tests were conducted in turning operation at various cutting speeds (450 – 650 m/min) and feed rate (0.05 – 0.15 mm/rev) under dry and MQL machining with uncoated carbide cutting tool. The average flank wear of cutting tool used in MQL reduced by 8.3%. The type of tool wear detected on the cutting tool were flank wear and crater wear, meanwhile adhesion, abrasion, (BUE) and (BUL) were among the wear mechanisms that can be observed on the tools. The surface roughness of the Al7075-T651 produced in MQL machining improved by 25% compared to in dry machining. Types of chips observed from various cutting parameter was continuous and discontinuous chips. In MQL machining, the chip thickness reduced by 6% - 11% at first cut of machining with new uncoated carbide cutting tool. At 50 minutes of machining time, the chip thickness in MQL machining reduced by 0.5% - 7.5%. The application of MQL was observed to be effective at cutting speed 450 m/min in reducing the coefficient of friction, with 6% - 11% reduction compared to dry machining. Meanwhile, at higher cutting speed, the coefficient of friction (CoF) was found to be 6% - 15% higher in MQL machining compared to dry. As the cutting progress, MQL application was found to be less effective by showing no specific trend in the resulting CoF. Thus, this study shows that the application of MQL in machining Al7075-T651 is beneficial to reduce the tool wear and improve the quality of surface finish but less favorable in reducing the CoF.